Pembuatan Aplikasi MOSTRANS Transporter Berbasis Mobile Menggunakan React-Native JavaScript - Rubin Salim; Desi Arisandi; Janson Hendryli (Jurnal Ilmu Komputer dan Sistem Informasi, 2022)
MOSTRANS Mobile Transporter, the mobile application in this paper aims to advance technology in the health supply chain ecosystem so that every part of the operation can be more efficient and modern. In dealing with this problem as well, MOSTRANS Mobile Transporter aims to meet the needs of MOSTRANS Software as a Service (SaaS) clients by assisting them in carrying out their daily operational activities by answering problems such as what features are needed. This application is built using JavaScript and React-Native for the front-end. With GraphQL as a complementary component for the back-end. To test this application, the Black Box Testing method is used as well as testing by the user with the User Acceptance Test to ensure the application can be used for everyday use. From the test results, it was concluded that the application created had fulfilled the purpose of assisting the operational activities of the MOSTRANS SaaS client by facilitating the features required by the MOSTRANS SaaS client. By making this application, the daily operational activities of the parties involved will be much more efficient and mobile..